Efektivitas Salep Jintan Hitam (Nigella Sativa) Pada Proses Penyembuhan Luka Perineum Rupture Ibu Nifas - Yuniarti Yuniarti (Politeknik Kesehatan Kemenkes Mamuju, 2018)
Background The main cause of maternal mortality in Indonesia in the bearing process is infection. Eleven per cent of the infection come from bad treatment of perineum rupturee. There are about 85% women bearing through spontaneuous pervaginam experience perineum trauma and 1% of them are infected. Perineum rupture needs serious attention since it can cause woman reproduction organ disfunction and dead as the consequence of bleeding or sepsis. The procedure of perineum treatment still uses desinfectant lotion Povidon Iodin 10%, herbal oinment as additional wound protector and perineum pain killer. Because of this, the researcher is interested in studying the effectiveness of nigella sativa 10% and 15% in curing perineum rupture of postpartum mothers at puskesmas Jekan Raya, Central Kalimantan. Method Using Randomised pre-post test control group design, the 21 women suffering from perineum rupture stadium II are grouped into three. The black cumin (nigella sativa) oinment is rubbed on the wound Perineum rupture everyday during seven days of postpartum ranging from treatment group. The evaluation is done in the day 1 (pre test), the day 3, 5 and 7 (post test) by using REEDA scale. Result The black cumin (nigella sativa) oinment is effective in fastening wound healing of perineum rupture compared to control group (p<0,05). Conclusion The black cumin oinment (nigella sativa) in the inflammatory phase until the proliferation phase and can be recommended as an adjunct to the treatment of postpartum maternal perineal rupture wounds.